FRESH AND PRESERVED COCONUT MILK - Robert Hagenmaier (International Coconut Community, 1988)
This article was written with two goals. The first is to show that coconut milk is an important product, at least to those in volved in the production of coconuts. The second is to suggest how the market for preserved coconut milk might be expanded. We will first review how coconut milk is consumed, for what purposes and in what quantity. Next we will look at the different kinds of preserved coconut milk. Finally, we will consider how the market for preserved coconut milk might be bolstered by standardizing its quality.